Pengembangan prototipe sistem pengukuran KWH meter digital presisi komunikasi dua arah menggunakan short message service berbasis Mikrokontroler AT89S52 dan Atmega16 (Development of a two-way communication precision digital KWH meter measurement system prototype using a short message service based on the AT89S52 and Atmega16 microcontroller) - Yosep Permana; - Asrizal; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2013)
ABSTRACTMeasurement system of electrical energy of PLN customers is done manually can cause errors. These Errors can occur when reading the data of KWH meter and entering the data into customer database system. Based on this fact development of automatic KWH meter with Short Message Service is important. Digital KWH meter can measure electrical energy more precise, turn off electricity automatically and turn on it base on a database. In general, this research intend to design and develop a digital KWH meter with measurement system using the short message service with two direction of communication base on microcontroller AT89S52 and ATMega16. The data obtained through measurement is analyzed in two methods, namely by statistics and graphs. There are four results of this research, those are : 1. KWH meter consists of two parts, namely KWH Meter Digital System and System server for database, 2. Accuracy from rotation disk value, KWH value and cost of customer each are 100%, 99.30% and 100%, Precision from rotation disk value and KWH value each are 1 and 0.99, 3. Time to send data KWH to copy into customer database is 37.65s, 4. Time to turn of and turn on KWH meter each are 11.97s and 19.15s. Keywords : KWH meter, optocoupler sensor, short message service